Tanggung Jawab Notaris Atas Keabsahan Akta Otentik Yang Memakai Surrogate Sebagai Pengganti Tanda Tangan - Richard Angling Wibisono (LPPM Universitas Ekasakti Padang, 2024)
Notary is a public official who has the authority to make authentic deeds and has responsibility for the deed, an authentic deed made by and before a notary after being read out is then signed by the faces, witnesses, and notary. The problem arises when the confronter is unable to affix his signature due to either physical limitations, the confronter cannot read or write, or also the confronter has a signature that changes. For this problem, for those who cannot affix their signatures, the signatures can be replaced where at the end of the deed the notary provides a statement called a surrogate. This writing uses normative juridical research methods by conducting library research to obtain various legal materials and applicable laws and regulations. This writing aims to obtain the fact that notaries must be able to be responsible for the authentic deeds they make, whether it is affixed with signatures by the confronters or those who use surrogates as a substitute for signatures. It is hoped that through the use of surrogates in the deed, the confrontants will not experience differential treatment between one another so as to get the same sense of legal certainty and justice.